1991
DOI: 10.2134/agronj1991.00021962008300060021x
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate Interaction with Uptake and Leaf Concentration of Magnesium, Calcium, and Potassium in Winter Wheat Seedlings

Abstract: Low concentrations of Mg and Ca in cool-season grasses in late fall and early spring are a primary cause of grass tetany and wheat pasture poisoning in grazing cattle. Our objective was to investigate phosphate interaction with the uptake and leaf concentration of Mg, Ca, and Kin winter wheat (Triticum aestivum L., cv. Larned) seedlings. Seedlings were grown hydroponically or in pots containing perlite with a solution containing nutrient element concentrations that mimicked the soil solution of a typical midwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
14
1
2

Year Published

1993
1993
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 16 publications
6
14
1
2
Order By: Relevance
“…There was not a significant correlation between PO4-P and plant Ca or Mg concentration or Ca/P, K/(Ca + Mg), or K/Mg ratios for any of the harvests. These results are a reversal to the results of Reinbott and Blevins (1991) for winter wheat grown in low P, low pH systems.…”
Section: Resultscontrasting
confidence: 68%
See 1 more Smart Citation
“…There was not a significant correlation between PO4-P and plant Ca or Mg concentration or Ca/P, K/(Ca + Mg), or K/Mg ratios for any of the harvests. These results are a reversal to the results of Reinbott and Blevins (1991) for winter wheat grown in low P, low pH systems.…”
Section: Resultscontrasting
confidence: 68%
“…Studies on low available P and acid to neutral soils have suggested that increasing soil solution P levels would decrease the 1C/(Ca + Mg) ratio in grasses (Reinbott and Blevins, 1991), however under the conditions of this study on basic calcareous soils with adequate P, there was no correlation between available soil P and the cation uptake rates except for K in the first cutting, which would tend to raise the K/(Ca + Mg) ratio, had other factors remained constant.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the differences in the nutrients uptake, the level of potassium on the shoots decreased with application of P. REINBOTT & BLEVINS (1991) also observed this reduction of K in wheat seedlings. The level of magnesium on the shoots increases with application of P, behavior already described in the literature (ADAMS, 1980;MALAVOLTA, 2004;ROBSON & PITMAN, 1983).…”
Section: Resultssupporting
confidence: 56%
“…We reported that absorption of essential nutrient minerals was often enhanced by PTKPA in wheat and cabbage (Watanabe et al, 2002(Watanabe et al, , 2005. Reinbott et al (1991) and Skinner and Matthews. (1990) also observed an increase in absorption of Mg and Ca in wheat and grape plants under a high P condition.…”
Section: Mineral Contentmentioning
confidence: 99%